Specific Sialoforms Required for the Immune Suppressive Activity of Human Soluble CD52 - Shathili, Abdulrahman M.; Bandala-Sanchez, Esther; John, Alan; Goddard-Borger, Ethan D.; Thaysen-Andersen, Morten; Everest-Dass, Arun V.; Adams, Timothy E.; Harrison, Leonard C.; Packer, Nicolle H. (Frontiers in Immunology, 2019)
Human CD52 is a small glycopeptide (12 amino acid residues) with one N-linked glycosylation site at asparagine 3 (Asn3) and several potential O-glycosylation serine/threonine sites. Soluble CD52 is released from the surface of activated T cells and mediates immune suppression via its glycan moiety. In suppressing activated T cells, it first sequesters the pro-inflammatory high mobility group Box 1 (HMGB1) protein, which facilitates its binding to the inhibitory sialic acid-binding immunoglobulin-like lectin-10 (Siglec-10) receptor. We aimed to identify the features of CD52 glycan that underlie its bioactivity. Analysis of native CD52 purified from human spleen revealed extensive heterogeneity in N-glycosylation and multi-antennary sialylated N-glycans with abundant polyLacNAc extensions, together with mainly di-sialylated O-glycosylation type structures. Glycomic (porous graphitized carbon-ESI-MS/MS) and glycopeptide (C8-LC-ESI-MS) analysis of recombinant soluble human CD52-immunoglobulin Fc fusion proteins revealed that CD52 bioactivity was correlated with a high abundance of tetra-antennary α-2,3/6 sialylated N-glycans. Removal of α-2,3 sialylation abolished bioactivity, which was restored by re-sialylation with α-2,3 sialyltransferases. When glycoforms of CD52-Fc were fractionated by anion exchange MonoQ-GL chromatography, bioactive fractions displayed mainly tetra-antennary, α-2,3 sialylated N-glycan structures and a lower relative abundance of bisecting GlcNAc structures compared to non-bioactive fractions. In addition, O-glycan core type-2 di-sialylated structures at Ser12 were more abundant in bioactive CD52 fractions. Understanding the structural features of CD52 glycan required for its bioactivity will aid its development as an immunotherapeutic agent.